The Influence of Water Temperature and Soaking Duration at Two Levels of Fruit Maturity for Soursop (Annona muricata Linn) Seed Germination - Dea Triaspita Gea; Haryati Haryati; Jonatan Ginting (Jurnal Agroekoteknologi, 2018)
Seed maturity is the one of important factors in germination process. Physiologically immature seeds generally do not have sufficient food reserves and seed structure are not fully formed, which may inhibit germination processes. One effort that can be done to accelerate the process of seed germination to soaking seeds in the water. This research was conducted at the Laboratory of Seed Technology, Agriculture Faculty, North Sumatera University, Medan, from December 2016 to  February 2017, using a randomized block design with 3 factors. The first factor is fruit  maturity with 3 levels: immature; mature, the second factor is water temperature with 2 levels: 28⁰ C; 9⁰ C and the third factor is the length of soaking with 3 levels: 12 hours; 24 hours; 36 hours. The results interaction treatments fruit mature, water temperature 9⁰ C and soaking duration 36 hour significantly accelerate the germination rate to 20,45 days, increasing vigor index to 1,57 seed/days, increasing percentage normal seedling to 100,00% decreasing percentage abnormal seedling and seed dies to 0,00%.